2022
DOI: 10.3389/fpls.2022.984795
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fermentation of Qu on the digestibility and structure of waxy maize starch

Abstract: The fermentation of Qu (FQ) could efficiently produce enzymatically modified starch at a low cost. However, it is poorly understood that how FQ influences the waxy maize starch (WMS) structure and the digestion behavior. In this study, WMS was fermented by Qu at different time and starches were isolated at each time point, and its physico-chemical properties and structural parameters were determined. Results showed that the resistant starch (RS), amylose content (AC), the average particle size [D(4,3)] the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Wu et al . (2022) fermented waxy maize starch for 60 h and reported that SDS content increased up to 24 h and then decreased. In comparison with the 3 days, SDS content of 7 days did not significantly increase in some millets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al . (2022) fermented waxy maize starch for 60 h and reported that SDS content increased up to 24 h and then decreased. In comparison with the 3 days, SDS content of 7 days did not significantly increase in some millets.…”
Section: Resultsmentioning
confidence: 99%
“…SDS of control millets ranged from 9.80 to 27.59 g per 100 g whereas upon fermentation, it decreased up to 43.48% and 55.47% for 3 and 7 days respectively. Wu et al (2022) fermented waxy maize starch for 60 h and reported that SDS content increased up to 24 h and then decreased. In comparison with the 3 days, SDS content of 7 days did not significantly increase in some millets.…”
Section: In Vitro Starch Digestibility (Ivsd)mentioning
confidence: 99%
“…The stock solution (200 μl was placed in a 15 mL centrifuge tube, 0.1 mol/L hydrochloric acid solution (200 μl) was added to neutralize, iodine (200 μl) was added, distilled water (9.4 mL) was added, shaken and left for 20 minutes. The absorbance was measured at 620 nm and 510 nm by using a visible-light spectrophotometer (Lab Tech Ltd., Beijing, China) ( Wu et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…After lactic acid bacteria fermentation, the gelatinization temperature of sorghum starch decreased, peak viscosity (PV) increased, and in vitro digestibility of starch increased. 4 A similar studies have also found that the digestibility of starch decreased, 5 and the fermentation of Lactiplantibacillus plantarum A6 could reduce the content of rapidly digestible starch (RDS) and increase the content of resistant starch (RS), thus slowing down the digestion of sweet potato starch. 6 Many studies have shown that lactic acid bacteria fermentation has a significant impact on the structure and physicochemical properties of starch.…”
Section: Introductionmentioning
confidence: 91%